Impact of Web-Based Psychoeducation on Anxiety, Self-Efficacy, and Decision-Making Support of HPV Vaccination among Female Adolescents - Mutiar, Astri; Marfuah, Dewi; Lindayani, Linlin (The Malaysian Journal of Nursing (MJN), 2025)
Background: Cervical cancer in Indonesia is a major public health concern, with Human Papillomavirus (HPV) vaccination being a key preventive measure. However, psychosocial barriers like anxiety and low self-efficacy hinder vaccination uptake among female adolescents, requiring web-based psychoeducation interventions. Objective: This study aimed to evaluate the impact of a web-based psychoeducation programme on anxiety, self-efficacy, and decision-making support regarding HPV vaccination among female adolescents in Indonesia. Methods: A quasi-experimental study design was employed, involving 200 female adolescents aged 15–19 years, divided equally into intervention and control groups. The intervention group received a structured web-based psychoeducation programme, while the control group received standard information. Psychosocial outcomes were assessed using validated instruments: Generalised Anxiety Disorder-7 (GAD-7), General Self-Efficacy Scale (GSES), and Decision-Making Self-Efficacy Scale. Pre- and post-intervention data were analysed using paired t-tests, ANCOVA, and MANCOVA. Results: The intervention group showed significant improvements in anxiety reduction (mean difference: -9.7, p<0.001), self-efficacy enhancement (mean difference: 8.0, p<0.001), and decision-making support (mean difference: 7.9, p<0.001) compared to the control group. Effect sizes indicated moderate to strong impacts across all psychosocial dimensions. Conclusion: Web-based psychoeducation significantly improves psychosocial outcomes, including anxiety, self-efficacy, and decision-making support, among female adolescents. These findings highlight the potential of digital interventions in promoting HPV vaccination acceptance and addressing mental health challenges.